Investigating professional learning communities in Turkish schools: the effects of contextual factors. Issue 3 (27th May 2017) - Sukru Bellibas, Mehmet; Bulut, Okan; Gedik, Serafettin
Abstract : A great number of studies have focused on professional learning communities in schools, but only a limited number of studies have treated the construct of professional learning communities as a dependent variable. The purpose of this research is to investigate Turkish schools' capacity for supporting professional learning communities and to examine factors that account for variation in the current level of development. The data for this study were collected from 492 school staff members, including teachers, principals and assistant principals, working at 27 schools across nine provinces of Turkey. Results indicate that school staff had a culture of sharing and collaboration, but suffered from a lack of material and human resources required for supporting effective learning communities. The experience of the staff, as well as the size and socioeconomic status of the school, appeared to be the most important factors in predicting the variation in the available professional learning communities. The results are discussed considering current educational policy and practice in Turkey.